Spinal and somatic growth in patients with juvenile chronic arthritis treated for up to 2 years with deflazacort. - David, J; Loftus, J; Hesp, R; Ansell, B; Reeve, J; Woo, P (1992)
We previously reported a double-blind controlled trial of Deflazacort vs Prednisone in patients with Juvenile Chronic Arthritis who had required corticosteroid therapy for at least one year. This paper presents further results on an additional 11 patients, making 26 altogether, who were treated for one year with deflazacort. Fourteen of these went on to a second year of deflazacort treatment. As previously reported, the relative rate of spinal bone mineral growth in the first year was greater for the spinal bone mineral content than for the body surface by about 70%. In the second year of treatment spinal bone mineral continued, with wide variations, to grow at the same or a very slightly greater rate. However, somatic growth recovered so that there was no significant difference between the relative growth rates in the spinal bone mineral and the body surface area in year 2 (P = 0.78). Deflazacort therapy appears to permit appropriate growth of the spine in relation to the rest of the body against a background of variable growth impairment due to the disease process and the treatment required to control it.